The effects of folate supplementation on inflammatory factors and biomarkers of oxidative stress in overweight and obese women with polycystic ovary syndrome: a randomized, double‐blind, placebo‐controlled clinical trial. (15th April 2014) - Bahmani, Fereshteh; Karamali, Maryam; Shakeri, Hossein; Asemi, Zatollah
Summary Objective This study was conducted to determine the effects of folate supplementation on inflammatory factors and biomarkers of oxidative stress among women with polycystic ovary syndrome (PCOS). Design, Patients and Measurements This randomized, double‐blind, placebo‐controlled clinical trial was conducted among 69 women diagnosed with PCOS and aged 18–40 year old. Participants were randomly assigned to three groups receiving the following: (1) folate‐1: 1 mg/d folate supplements (N = 23); (2) folate‐5: 5 mg/d folate supplements (N = 23) and (3) placebo (N = 23) for 8 weeks. Fasting blood samples were taken at the beginning of the study and after 8 weeks to measure homocysteine (Hcy), inflammatory factors including high‐sensitivity C‐reactive protein (hs‐CRP), nitric oxide (NO), biomarkers of oxidative stress including total antioxidant capacity (TAC), glutathione (GSH), malondialdehyde (MDA) and homoeostatic model assessment‐beta cell function (HOMA‐B). Results Supplementation with 5 mg/d folate resulted in reduced plasma Hcy (−2·23 vs −1·86 and 1·16 μm, respectively, P < 0·05), HOMA‐B (−7·63 vs 1·43 and 13·66, respectively, P < 0·05), serum hs‐CRP (−212·2 vs −262·4 and 729·8 μg/l, respectively, P < 0·05) and plasma MDA concentrations (−0·48 vs −0·24 and 0·69 μm, respectively, P < 0·01) compared with folate‐1 and placebo groups. Furthermore, a significant rise in plasma TAC (0·64 vs −3·53 and −215·47 mm, respectively, P < 0·01) and GSH levels (162·1 vs 195·8 and −158·2 μm, respectively, P < 0·01) was also observed following the administration of 5 mg/d folate supplements compared with folate‐1 and placebo groups. Conclusions In conclusion, folate supplementation (5 mg/d) in women with PCOS had beneficial effects on inflammatory factors and biomarkers of oxidative stress.